2019
DOI: 10.1097/inf.0000000000002254
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Childhood Otorrhea in Luanda, Angola, and a Review of Otitis Media in African Children

Abstract: Background: In resource-poor settings, otorrhea causes a significant burden of disease in children. Etiologic studies and structured data on otorrhea and chronic otitis media among African children remain scarce. Methods: Here, we reviewed 678 bacteriologically analyzed otorrhea samples from Luanda Children's Hospital from children ≤15 years of age bet een 2008 and 2015. We then compared these to data from other studies among African children through a literature review of 20 papers published over two decades.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…aureus (5%–14%). In our result the most common pathogen causing otorrhoea was Proteus, which is in correspondence with the literature review from Africa 20 . In studies from Kenya for instance, Proteus is frequently detected as the most common agent causing otorrhoea among children and young adults 21 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…aureus (5%–14%). In our result the most common pathogen causing otorrhoea was Proteus, which is in correspondence with the literature review from Africa 20 . In studies from Kenya for instance, Proteus is frequently detected as the most common agent causing otorrhoea among children and young adults 21 .…”
Section: Discussionsupporting
confidence: 89%
“…In our result the most common pathogen causing otorrhoea was Proteus, which is in correspondence with the literature review from Africa. 20 In studies from Kenya for instance, Proteus is frequently detected as the most common agent causing otorrhoea among children and young adults. 21 In our study, the most common pathogens found in the ear discharge of the children with BM were likely to be related more to chronic than acute middle ear infections.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, the highest incidence rates for AOM (43 per 1000) and CSOM (4.79 per 1000) are found in the Central African region and Angola [7]. The prevalence rates of CSOM are consistently reported to exceed the magnitude of a public health concern [4, 9].…”
Section: Introductionmentioning
confidence: 99%
“…(37%), Pseudomonas spp. (13-15%) and S. aureus (5-14%) 22 . We found that the most common pathogen causing otorrhea was Proteus, which is in correspondence with the literature review from Africa 22 .…”
Section: Discussionmentioning
confidence: 99%
“…(13-15%) and S. aureus (5-14%) 22 . We found that the most common pathogen causing otorrhea was Proteus, which is in correspondence with the literature review from Africa 22 . In studies from Kenya for instance, Proteus is frequently detected as the most common agent causing otorrhea among children and young adults 23,24 .…”
Section: Discussionmentioning
confidence: 99%